2016
DOI: 10.1111/dme.13079
|View full text |Cite
|
Sign up to set email alerts
|

Young people with Type 1 diabetes of non‐white ethnicity and lower socio‐economic status have poorer glycaemic control in England and Wales

Abstract: The association between ethnicity and glycaemic control persists after adjustment for deprivation and pump use. An alternative approach to intensive insulin therapy might benefit these vulnerable children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 27 publications
(38 reference statements)
3
26
1
1
Order By: Relevance
“…Because the majority of our families were of Dutch origin and fairly highly educated (38), future research should aim to examine more diverse cohorts in terms of ethnicity, education, and socioeconomic status. As previous studies showed that low socioeconomic status and belonging to a minority ethnic group are associated with less optimal diabetes outcomes, study results may be more pronounced in a more diverse cohort (39,40).…”
Section: Discussionmentioning
confidence: 73%
“…Because the majority of our families were of Dutch origin and fairly highly educated (38), future research should aim to examine more diverse cohorts in terms of ethnicity, education, and socioeconomic status. As previous studies showed that low socioeconomic status and belonging to a minority ethnic group are associated with less optimal diabetes outcomes, study results may be more pronounced in a more diverse cohort (39,40).…”
Section: Discussionmentioning
confidence: 73%
“…36 Higher rates of CSII use are reported in girls, whereas those from ethnic minorities and the most deprived patients are least likely to use CSII, even in health-care settings with universal funding. [37][38][39] In these studies, lower socioeconomic status and ethnicity were also predictors of poorer glycaemic control, even when the effect of CSII use was accounted for. This demonstrated that the characteristics of those who use CSII are the same as the characteristics that facilitate good glycaemic control, raising important issues of bias.…”
Section: National Database Reportsmentioning
confidence: 86%
“…We noted that the small number of patients and parents who declined to participate in the study, stating a strong preference for CSII (n = 36), had a higher deprivation index (were more deprived) than those who declined stating a strong preference for MDI (n = 259) and those who participated in the study. National database studies [37][38][39] report an association with CSII use and deprivation, with the most deprived patients being least likely to be treated with CSII. Our data suggest that this association is established sometime later after the diagnosis of T1D.…”
Section: Patient Recruitment and Retentionmentioning
confidence: 99%
“…However, similar to that seen in the completion of healthcare checks, there is considerable variability in HbA1c outcomes seen across centres delivering care (figure 2B). Although some of this variability may be due to different case-mix between centres providing care (eg, social deprivation, age, duration of diabetes and ethnicity8), the audit analysis tries to take this into account, utilising the case-mix variables to provide an adjusted clinical mean HbA1c. However, <10% of the variability in outcomes is related to such measurable factors, with the rest assumed to come from the influence of the clinical set-up (figure 2B).…”
Section: Outcomes Of Carementioning
confidence: 99%